Size Reduction of Wilkinson Power Divider using a Combination of Parallel Coupled Lines and Defective Microstrip Structures - B. P. Eppe; A. Ghosh; P. Mondal (Advanced Electromagnetics)
This work describes a miniaturized power divider (PD) using the combination of two symmetrical parallel coupled lines (PCL) and a defective microstrip structure (DMS). The proposed PD is intended for 2.4 GHz wireless local area network (WLAN) applications. DMS structures are used to improve PD performance while also decreasing its size. Initially, to reduce the circuit size, quarter-wavelength lines were replaced with PCL’s. It is observed that the size of PD is 0.42λgX0.53λg, representing a 25.3% decrease. Furthermore, four DMS structures are integrated into the design to reduce the overall size by 43% as compared with conventional Wilkinson PD at 2.4 GHz. The final size of PD is 0.35λgX0.47λg. Required equations are provided for the optimization of the DMS structure. The proposed PD has a return loss, isolation performance, and power division of around 16 dB, -15 dB, and -3.3 dB, respectively. The designed PD is fabricated on the substrate of Rogers RT/duroid 5880 with εr=2.2.